Youtube and the development of the mathematical competence. results of a quasiexperimental investigation - Antonia Ramírez García (Universidad de La Rioja, 2013)
The aim of this paper is to present the results reached in mathematical competence by students of quarter of primary education in an educational center that has taken part during the course 2008/09 in a quasiexperimental investigation financed by the Commission of Education of the Junta of Andalusia. The objetive of this investigation was to increase the mathematical competence of the students -resolution of problems related to the daily life, knowledge of the mathematical basic elements in situations real or simulated (measurements and geometric elements), application of algorithms, argumentations, etc.-, using a methodology based on groups of level curricular and to attend on his diversity; at the same time, the incorporation of the Web 2.0 to different didactic implemented units has led us to determining factors of influence in the mobilization of mathematical competence, such as the use of the digital, decisive video in the comprehension of the dynamic geometry.